Simulation of a throwing device for wrestlers - Koshkin, E.; Solonitsin, R.; Smirnov, A.; Kruchinina, K. (Human. Sport. Medicine, 2020)
Aim. The paper aims to develop a model of a training device for wrestlers that helps to improve technique and special physical fitness. Materials and Methods. The study investigates the process of developing technical skills and special physical fitness in wrestlers. The following research methods were applied: analysis of scientific and methodical literature and practical experience, pedagogical observation, pedagogical experiment. The efficacy of the device was tested together with the Perm Krai federation of sports and combat sambo during 2018-2019 academic year. Thirty wrestlers aged from 14 to 16 years participated in the study (CG, n = 15; EG, n = 15). All wrestlers were of different weight categories and possessed a title of Candidate for Master of Sport. Results. The results of the pedagogical experiment testify to a significant advantage (p < 0.05) of sambo wrestlers in the experimental group over sambo wrestlers in the control group in terms of special physical fitness. Competitive activity of the experimental group is more stable, and the growth of sportsmanship is higher than that of the control group. Conclusion. The authors developed a model of a training device for wrestlers to improve their technical skills and special physical fitness. However, the engineering and technical component of the training device is not perfect and requires further improvement.